2017
DOI: 10.1371/journal.pgen.1006566
|View full text |Cite
|
Sign up to set email alerts
|

KLK5 and KLK7 Ablation Fully Rescues Lethality of Netherton Syndrome-Like Phenotype

Abstract: Netherton syndrome (NS) is a severe skin disease caused by the loss of protease inhibitor LEKTI, which leads to the dysregulation of epidermal proteases and severe skin-barrier defects. KLK5 was proposed as a major protease in NS pathology, however its inactivation is not sufficient to rescue the lethal phenotype of LEKTI-deficient mice. In this study, we further elucidated the in vivo roles of the epidermal proteases in NS using a set of mouse models individually or simultaneously deficient for KLK5 and KLK7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 48 publications
7
62
0
Order By: Relevance
“…Specifically, it was shown that persistent inflammation and TSLP production in atopic dermatitis (AD) is induced by KLK5 in a PAR2-independent manner [28]. On the other side, the latter study [28] confirmed that KLK5 plays an important role in DSG1 degradation as has been shown previously [13,24] further substantiating the key role of KLK5 in the desquamation process.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Specifically, it was shown that persistent inflammation and TSLP production in atopic dermatitis (AD) is induced by KLK5 in a PAR2-independent manner [28]. On the other side, the latter study [28] confirmed that KLK5 plays an important role in DSG1 degradation as has been shown previously [13,24] further substantiating the key role of KLK5 in the desquamation process.…”
Section: Discussionsupporting
confidence: 68%
“…Deletion of Klk6 restored normal epidermal differentiation patterns in Spink5 À/À epidermis. Previously, it was shown that deletion of Klk7 in Spink5 À/À mice did not prevent epidermal overdesquamation but it normalized epidermal differentiation and inflammation [24], suggesting that Klk6 and Klk7 may have common functions in skin. Since KLK7 is not able to activate PAR2 [25] this finding indicates that, probably, there are other yet unknown PAR2-independent pathways that regulate the induction of inflammation by KLKs in the epidermis.…”
Section: Discussionmentioning
confidence: 98%
“…As shown by Fortugno et al ., LEKTI is processed into different active domains by the enzyme furin . Moreover, there is increasing evidence that it is mainly loss of KLK5 control that drives the phenotype of Netherton syndrome . Now we confirm that the LEKTI domains D6, D7 and D8+9 are active inhibitors of KLK5, and we show that these fragments are substrates for TG1.…”
Section: Discussionsupporting
confidence: 66%
“…NGP (Neutrophilic granule protein) or ‘bectenecin’ – also belongs to cathelicidins, has a cathelicidin protein domain, and in our data, it is also significantly up-regulated in metestrus (2.8 fold), likely because it is co-expressed with CAMP in neutrophils which invade vaginal environment during metestrus. CAMP is regulated by the serine-proteases Kallikreins 5 and 7 55 and thus belongs to an extended KLK/LEKTI network members that are crucial for homeostasis of stratified epithelia 56 . We did not detect KLK5 and KLK7 in the vaginal secretion.…”
Section: Resultsmentioning
confidence: 99%